Plant production of a virus-like particle-based vaccine candidate against porcine reproductive and respiratory syndrome - VanderBurgt, Jordan T.; Harper, Ondre; Garnham, Christopher P.; Kohalmi, Susanne E.; Menassa, Rima (Frontiers in Plant Science, 2023)
Porcine reproductive and respiratory syndrome (PRRS) is a disease leading to spontaneous abortions and stillbirths in sows and lowered life quality and expectancy in growing pigs. PRRS is prevalent worldwide and has significant economic impacts to swine industries around the globe. Co-expression of the two most abundant proteins in the viral envelope, the matrix protein (M) and glycosylated protein 5 (GP5), can produce a neutralizing immune response for the virus providing a potentially effective subunit vaccine against the disease, but these proteins are difficult to express. The goal of this research was to display antigenic portions of the M and GP5 proteins on the surface of tobacco mosaic virus-like particles. A modified tobacco mosaic virus coat protein (TMVc) was transiently expressed in Nicotiana benthamiana leaves and targeted to three subcellular compartments along the secretory pathway to introduce glycosylation patterns important for M GP5 epitope immunogenicity. We found that accumulation levels in the apoplast were similar to the ER and the vacuole. Because glycans present on plant apoplastic proteins are closest to those present on PRRSV proteins, a TMVc M GP5 fusion construct was targeted to the apoplast and accumulated at over 0.5 mg/g of plant fresh weight. TMVc virus like particles self assembled in plant cells and surface-displayed the M-GP5 epitope, as visualized by transmission electron microscopy and immunogold localization. These promising findings lay the foundation for immunogenicity and protective-immunity studies in animals to examine the efficacy of this vaccine candidate as a measure to control PRRS.